2019
DOI: 10.5696/2156-9614-9.22.190602
|View full text |Cite
|
Sign up to set email alerts
|

Human Health Risk and Bioaccessibility of Toxic Metals in Topsoils from Gbani Mining Community in Ghana

Abstract: Background. Anthropogenic activities such as artisanal mining pose a major environmental health concern due to the potential for discharge of toxic metals into the environment. Objectives. To determine the distribution and pollution patterns of arsenic (As), iron (Fe), nickel (Ni), cobalt (Co), chromium (Cr), manganese (Mn), copper (Cu) and zinc (Zn) in the topsoil of a mining community in Ghana, along with potential human health risks and in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 32 publications
0
7
1
Order By: Relevance
“…Mikutta et al (2014) and Palumbo-Roe and Klinck (2007) reported BAF of As as 5-34% and 0.5-42% in mine impacted soils in Bulgaria and south England respectively, which is in close range with this study. On the other hand, samples in present study showed higher BAF for Cu and Ni compared to other mining areas (Darko et al, 2019;Karadaş and Kara, 2011). Furthermore, BAF for Cd, Pb and Zn in our study is comparable to those reported by Roussel et al (2010) on smelter contaminated urban soil in northern France.…”
Section: Total and Bioaccessible Concentrations Of Pte In The <250 µM Fraction Of The Waste Rock Tailings And Soilcontrasting
confidence: 57%
“…Mikutta et al (2014) and Palumbo-Roe and Klinck (2007) reported BAF of As as 5-34% and 0.5-42% in mine impacted soils in Bulgaria and south England respectively, which is in close range with this study. On the other hand, samples in present study showed higher BAF for Cu and Ni compared to other mining areas (Darko et al, 2019;Karadaş and Kara, 2011). Furthermore, BAF for Cd, Pb and Zn in our study is comparable to those reported by Roussel et al (2010) on smelter contaminated urban soil in northern France.…”
Section: Total and Bioaccessible Concentrations Of Pte In The <250 µM Fraction Of The Waste Rock Tailings And Soilcontrasting
confidence: 57%
“…Furthermore, acidification affects the structure and functioning of ecosystems (Carlson, 2013;Bonilla et al, 2018;Simate, 2021). Bioaccumulation and biotransformation of toxic HM and metalloids (e.g., As, Pb, Cr, Cd, and Hg) along the food chains that may constitute a serious public health risk associated with AMD pollution have also been reported in literature (Emmanuel et al, 2018;Darko et al, 2019;Gwenzi, 2020;Chan et al, 2021;Yang et al, 2021). The main effects of HM on human health range from bronchitis, skin and bladder cancer, liver and kidney failure, to mental retardation in children (Rambabu et al, 2020).…”
Section: Environmental and Health Impacts Of Amd Pollutionmentioning
confidence: 93%
“…Enrichment factor values for both metals were higher than 1 at site-4 and site-5. The results showed the Zn and Fe enrichment in the study area due to mining activities which was lower than Darko et al (2019) and Barakat et al (2012). Taha et al (2013) reported the higher Zn enrichment (12.1 mg/kg) than the current investigation.…”
Section: Discussionmentioning
confidence: 51%